2012
DOI: 10.1021/jp303651e
|View full text |Cite
|
Sign up to set email alerts
|

Cation Effect on the Electronic Excited States of Guanine Nanostructures Studied by Time-Resolved Fluorescence Spectroscopy

Abstract: International audienceThe effect of metal ions on the excited states of guanine nanostructures, short d(TG4T)4 quadruplexes and long G4-wires, are studied by fluorescence spectroscopy. The steadystate emission spectra show that both systems exhibit a strong cation effect. Fluorescence decays and fluorescence anisotropy decays, recorded from the femtosecond to the nanosecond timescale, reveal the following picture. In the presence of K+, emission arises mainly from delocalized ππ* states (excitons), whose decay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
109
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(122 citation statements)
references
References 47 publications
12
109
1
Order By: Relevance
“…Interestingly, we reproduce almost quantitatively the experimental hypochromic effect of the absorption maximum, which suggests that two stacked tetrads are a fairly reliable model also of longer species, especially when thinking that in TG 4 T edge effects and thermal fluctuations decrease the probability that a larger number of tetrads are strongly stacked. In agreement with experimental results, these features are similar for Na + and K + cations 33. The very good agreement with the experimental spectra indicates that M052X can model accurately the effect of the stacking and the hydrogen bonds on G excited states, and supports the reliability of our assignment.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Interestingly, we reproduce almost quantitatively the experimental hypochromic effect of the absorption maximum, which suggests that two stacked tetrads are a fairly reliable model also of longer species, especially when thinking that in TG 4 T edge effects and thermal fluctuations decrease the probability that a larger number of tetrads are strongly stacked. In agreement with experimental results, these features are similar for Na + and K + cations 33. The very good agreement with the experimental spectra indicates that M052X can model accurately the effect of the stacking and the hydrogen bonds on G excited states, and supports the reliability of our assignment.…”
Section: Resultssupporting
confidence: 87%
“…25 On the other hand, a detailed atomistic description of the nature and properties of the absorbing excited states of G‐Quads, which are responsible for the peculiar optical and CD spectra,1925 is still lacking. Analogously, experiments have shown that the minima responsible for the fluorescence spectra are very different from isolated G,32, 33 but their structures are completely unknown. Time‐resolved experiments show that the excited‐state lifetimes of G‐Quads are orders of magnitude greater than that of G,32, 33 but no description, even qualitative, of their decay paths is available, and the roles played by key factors such as the nature of the cation or the quadruplex topology have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics were also observed in the detailed measurements of GQS emission by Markovitsi and co-workers, who studied structures formed from assembly of four DNA oligonucleotides 50,66,71 and from the human telomeric sequence Tel21 (dGGGTTAGGGTTAGGGTTAGGG). 57 The steadystate emission of Tel21 is compared to our default system dG 3 T in Figure 7.…”
Section: ■ Discussionmentioning
confidence: 60%
“…nanostructures and energy transfer in DNA quadruplexes, 71,72 to the best of our knowledge no report is available on the metal ion regulated blue uorescence of guanosine gels. The morphological insight of G and dG gels was characterized using transmission electron microscopy (TEM).…”
Section: Resultsmentioning
confidence: 99%